Magnetic Constraints on Off‐Axis Seamount Volcanism in the Easternmost Segment of the Australian‐Antarctic Ridge - Hakkyum Choi; Seung‐Sep Kim; Sung‐Hyun Park (Geochemistry, Geophysics, Geosystems, 2021)
Abstract The Australian‐Antarctic Ridge (AAR) is an intermediate‐spreading rate system located between the Southeast Indian Ridge and Macquarie Triple Junction of the Australian‐Antarctic‐Pacific plates. KR1 is the easternmost and longest AAR segment and exhibits unique axial morphology and various volcanic structures. We identified three asymmetric seamount chains positioned parallel to the seafloor spreading direction, which were indicative of prevalent off‐axis volcanism in the vicinity of segment KR1. Two‐dimensional magnetic modeling was used to predict the magnetization polarity of the seamounts, as well as to constrain their formation time and duration. The magnetic modeling revealed that the majority of the examined seamounts were formed over a period of less than ∼600 kyrs. The seamount formation primarily occurred during two distinct volcanic pulses from 0.16–1.14 to 1.58–2.69 Ma. A temporal gap of 200–650 kyrs between the formation time of the seamounts and seafloor was estimated for certain seamounts that were formed much later than their underlying seafloor and at a distance of 10–20 km from the KR1 axis. Typically, such off‐axis seamount activity is related to axial mantle convection caused by excessive magma supply near the ridge crest. Considering the scale of off‐axis volcanism and thickening lithosphere ∼20 km away from the axis with intermediate‐spreading rates, small‐scale upwelling made feasible by the fertile mantle heterogeneity is proposed as the mechanism for the seamount formations at off‐axis distances, and the geochemically enriched compositions of the seamounts support this alternative explanation.